2017
DOI: 10.1080/02813432.2017.1288814
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in decision-making about cardiovascular preventive drugs – resistance as agency

Abstract: ObjectiveThe aim of the study was to describe and explore patient agency through resistance in decision-making about cardiovascular preventive drugs in primary care.DesignSix general practitioners from the southeast of Sweden audiorecorded 80 consultations. From these, 28 consultations with proposals from GPs for cardiovascular preventive drug treatments were chosen for theme-oriented discourse analysis.ResultsThe study shows how patients participate in decision-making about cardiovascular preventive drug trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…While few in number, implementation studies on SDM interventions in Sweden have suggested the importance of expanding the decision-making process beyond single encounters (Hultberg & Rudebeck, 2017) and beyond simply educating the patient in self-care (Herlitz, Munthe, Törner, & Forsander, 2016). Results from somatic care studies suggest that successful implementation of SDM requires continuity of care and that the user is offered concrete opportunities to participate as an equal in the decision-making process (Elwyn, Frosch, & Kobrin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While few in number, implementation studies on SDM interventions in Sweden have suggested the importance of expanding the decision-making process beyond single encounters (Hultberg & Rudebeck, 2017) and beyond simply educating the patient in self-care (Herlitz, Munthe, Törner, & Forsander, 2016). Results from somatic care studies suggest that successful implementation of SDM requires continuity of care and that the user is offered concrete opportunities to participate as an equal in the decision-making process (Elwyn, Frosch, & Kobrin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting qualitative study by Hultberg et al enlightens patient agency through resistance in decision-making about cardiovascular preventive drugs. One of their findings was that the recognition of active or passive resistance is valuable for a shared decision-making and that it supports personal agency [27].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence rate ratios suggested that patients with the lowest CoC had a higher number of emergency services visits compared with those experiencing the highest CoC [ 25 ]. Furthermore, Hultberg and Rudebeck [ 26 ] investigated patient participation in decision-making about cardiovascular preventive drug treatments through the resistance to treatment proposals in Sweden, concluding that the decision-making process extends beyond single encounters, which underpins the importance of CoC. Other studies found that CoC with a general practitioner is associated with lower healthcare costs, higher patient satisfaction and improvements in patient health [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%